High immunogenicity of nicotine vaccines obtained by intradermal delivery with safe adjuvants - Chen, Xinyuan (2012)
Immunotherapy for tobacco addiction may offer a safe, alternative treatment if the immunogenicity of the current nicotine vaccines can be improved. We show here that intradermal (ID) immunization induces the production of antibody directed against nicotine (NicAb) at a much higher level than conventional intramuscular (IM) immunization. The magnitude and duration of NicAb production was further increased robustly by non-inflammatory laser vaccine adjuvant (LVA), slightly inflammatory monophosphoryl lipid A (MPL) or a combination of MPL and CpG adjuvants. Consequently, significantly fewer vaccination doses were required to attain a high level of NicAb production for an extended period of time and reduce nicotine entry into the brain in the presence of LVA, MPL or MPL/CpG adjuvant, respectively. Yet, the potency of these adjuvants to augment ID nicotine vaccine immunogenicity came at the expense of local skin reactogenicity, with LVA causing little skin reaction and MPL/CpG stimulating overt skin irritation. These observations underscore a necessity of a balance between optimal adjuvant potency and undesired local reactogenicity. In summary, our study presents a novel approach to significantly improve nicotine vaccine immunogenicity by a combination of safe cutaneous vaccine adjuvants with ID immunization.